Association between the degree of Osteoarthritis and pain level of patients at Baptist Hospital, Batu City - Panji Sananta; Hansel Hansel; Dhelya Widasmara; Eka Noviya Fuzianingsih (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Osteoarthritis is a chronic disease characterized by the destruction of cartilage in the joints, causing stiffness, pain, and impaired movement. The condition most commonly affects the joints of the knees, hands, feet, spine, and often the shoulders and hips. Knee osteoarthritis is a major public health problem that causes chronic pain and reduces physical function and quality of life. This study determined the relationship between the degree of Osteoarthritis and the pain level in patients at Baptist Hospital, Batu City. This research used a cross-sectional study with 31 respondents. Data collection was conducted directly using the WOMAC (Western Ontario and McMaster Universities Osteoarthritis Index) questionnaire, modified in Indonesian. To determine the grade of Osteoarthritis using the Kellgren-Lawrence system. The results showed that out of 31 respondents, there were nine patients (29%) who had grade 1 osteoarthritis, 12 patients (38.7%) had grade 2, and 10 patients (32.3%) had grade 3. There were 22 patients (71%) who had a mild pain level, four patients (13%) had a moderate level, and five patients (16%) had a severe pain level. The Spearman correlation test showed no significant relationship (p>0.05) between the degree of Osteoarthritis and the level of pain in patients. This study concludes that there was no relationship between the increasing degree of Osteoarthritis and the level of pain.